The labour market impact of adult training among jobseekers in the county of Szabolcs-Szatmár-Bereg - Le-Dai, Barbara (Studia Mundi – Economica, 2022)
Szabolcs-Szatmár-Bereg county is one of the counties with one of the worst economic indicators in Hungary. The high unemployment rate and the low employment rate have forced the Hungarian Government to retrain job seekers. My analysis, based on secondary databases, examined the spatial inequalities in participation in training programmes and their impact on the labour market. With the introduction of public employment, the job placement rate of jobseekers in training in the primary labour market started to decline. The territorial analysis revealed that the county capital has the largest number of trained workers and that the border and rural areas had a negligible number of trained workers, with the result that municipalities with a high number of jobseekers were not affected by retraining where it was most needed.